COMPARATIVE EFFECTIVENESS OF CONTEXTUAL AND STRUCTURAL METHOD OF TEACHING VOCABULARY - Malik Ghulam Behlol (Universitas Katolik Indonesia Atma Jaya, 2010)
The study was conducted to find out the effectiveness of contextual and structural method of teaching vocabulary in English at secondary level. It was an experimental study in which the pretest posttest design was used. The population of the study was the students of secondary classes studying in Govt. Secondary schools of Rawalpindi District. Purposive and random sampling was applied to select the school and subjects. The significance of difference between the scores of groups at 0.05 level was tested applying t–test. The study revealed that the contextual method is more useful for high achievers (HA) whereas structural method is more useful for average and low achievers. The HA performed better with the contextual method due to the study of words in different contexts and taking help from contextual clues that has prompted spoken and written fluency. Better performance of the average and low achievers with the structural method was due to the morphological analyses of a word, the role of the students as the partner in the learning process, the generation and active processing of vocabulary, the provision of multiple exposure of different intensity for practice and personalization of word learning.Keywords: Vocabulary, effectiveness, contextual method, structural method.